Os interditos possessórios e aplicabilidade da antecipação dos efeitos da tutela em tais ações - Pinto, José André Machado Barbosa (2007)
When the thought of a State of Law arises, there is an absolute certainty that public order, social peace and the respect of a State s sovereignty are basic public interests protected by the Judiciary. The possession of land is a factual situation and a component of social stability, being, thus, the protection of the right of possession is a means of social pacification. If the possessor changes, that alteration cannot result in social disorder. It is imposed that the passage of possession form one subject to another be done without any risk to social harmony. When the dispute over the possession of land occurs, it must de dealt with by the due process of law, exactly as disciplined by the brazilian legislation. It is well known that the law flourishes within the evolution of social facts in society, and that justice should be swift and effective, or risk being characterized as manifest injustice, as Rui Barbosa (1849-1923) once said in his speech Oração aos Moços . In the mist of that absolute truth, the present dissertation aims to study the procedural remedies for protecting the rights of the possessor of land, and the applicability of the article 273 of the brazilian procedural code in those types of actions, both in cases involving posse nova (possession up to one year of duration) and posse velha (possession over one year of duration). The implementation of that institute results in more swiftness and effectiveness. To better illustrate that thought, it should be remembered the biblical passage in Matthew, chapter 22, verses 20 and 21, in which Jesus, after being questioned about the validity of the paying of taxes, affirms that what belong to Cesar should be given to Cesar, showing that justice is giving each person that which belongs to them, but also in a swift and effective manner, so as to avoid the manifest injustice that was referred to by Rui Barbosa